Central Bank Independence and Macroeconomic Performance: Implications for Current Account Deficit in Indonesia - Habibi, Amzar (Riviera Publishing, 2026)
Central bank independence (CBI) has long been promoted as an institutional arrangement to enhance macroeconomic stability, particularly through inflation control. However, empirical evidence regarding its impact on broader macroeconomic indicators—such as economic growth, government budget deficits, and current account deficits (CAD)—remains inconclusive, especially in developing economies. This study investigates the effects of CBI on macroeconomic performance and examines its policy implications for addressing Indonesia’s current account deficit. Using panel data from 182 countries over the period 1970–2012, this study applies a quasi-experimental approach through Regression Discontinuity Design (RDD). Central bank independence is measured using legal indices, namely the Legal Variable Aggregate Unweighted (LVAU) and Legal Variable Aggregate Weighted (LVAW). Thresholds distinguishing lower and higher levels of CBI are determined empirically using k-means clustering. The findings indicate that higher central bank independence has a statistically significant but relatively small negative effect on inflation. In contrast, CBI does not show a significant impact on economic growth, government budget deficits, or current account deficits. These results suggest that while central bank independence enhances the credibility of monetary policy in achieving price stability, it is not sufficient to directly address structural macroeconomic imbalances such as current account deficits. For Indonesia, the findings imply that Bank Indonesia’s primary mandate should remain focused on inflation control. Improvements in the current account balance require coordinated fiscal, structural, and trade policies beyond the scope of monetary policy alone.